A Situation Analysis of Higher Secondary Tribal Residential Schools in Tiruvannamalai District, Tamil Nadu, India - Bala Krishnan S; S. Sudharsan (Asian Social Work Journal, 2020)
Education for tribal communities has become one of the prime focuses which is taken into account as an integral a part of socio-economic development of Schedule Tribes in Asian country. Within the recent years, there has been some improvement in providing the education for the tribal communities. The implementation of Government Tribal Residential Schools has an important role to play in raising literacy rate. With regard to the literacy rate of the tribes in Tamil Nadu is 54.34 percent. As 83.08 per cent of the tribal survives in hilly/rural areas and 16.91 per cent of them live in urban (town) areas. (2011 Census). The status of Education in Tamil Nadu for Scheduled Tribe is worser than other states of the country. Tamil Nadu is ranked third compared to all over literacy rate. In case of ST (41.53%) still it is lower than the general sections(73.57%) of the society. The socio-economic backwardness, lack of good education facility and asymmetrical structure of the society are the reasons for being lower caste of ST. The objective of the study is to understand the impact of the Tribal residential school, set up within the tribal area of Jawadhi a hilly area in the District Tiruvannamalai. And also, the challenges faced by the students in the school. Data was collected through Interview and observation. This study intends to evaluate the Tribal Residential School with the objective to find whether the design of programme is appropriate to meet the stated objectives, whether there is any impact in decreasing the dropout rates of STs. Moreover, it will also reveal about the efficacy with which the mechanism of education promotion is pending in the process of implementation and the need for the efficient mechanism to develop it for the empowerment of tribes. The main objective of residential schools for Scheduled Tribes (STs) students is to provide quality education to tribal students. The study suggests, to follow the guidelines that indicate the organizational structure, Manpower and Educational expertise for the Tribal welfare Department. All these tribal residential school should have separate budget plan for infrastructure, recurring, non-recurring expenditure every year and it should be included in the annual work plan & budget.